Clinical and epidemiological features of patients with multiple sclerosis in the Kursk Region - V. B. Laskov; E. A. Logacheva; E. E. Tretyakova; M. A. Gridnev (Неврология, нейропсихиатрия, психосоматика, 2017)
Objective: to analyze the regional register of patients with multiple sclerosis (MS) in the Kursk Region in terms of gender- and age- related characteristics of patients, the degree of their disability and a range of prescribed disease-modifying drugs (DMDs) used to treat MS.Patients and methods. Data on 877 patients included in the regional MS register in 2014–2016 were analyzed. The diagnosis of MS was substantiated by the McDonald criteria edited by C.H. Polman and evidenced by brain magnetic resonance imaging. A total of 793 (91.4%) patients, of whom 529 (66.7%) received DMDs for MS, were actively followed up.Results and discussion. The Kursk Region was established to be a high-risk area for MS; territories with its maximum and minimum prevalence were determined. MS cases were 2.5 times more common among women. The risk factors for MS in the region were as follows: female gender (except for the age of 26–30 years) and urban residence; the role of genetic characteristics and exposure to pesticides and industrial allergens was also possible. The relationship of the symptomatic onset of MS to age in males and females has its own characteristics in the region. The pattern of disability was studied in patients. Glatiramer acetate and interferons were most frequently prescribed as DMDs for MS in the region.Conclusion. The findings may be used to plan drug supply for patients with MS and the work of sociomedical examination service and to enhance the efficiency of organizing the treatment with and use of DMD for MS in the region.